2015
DOI: 10.1136/bjophthalmol-2015-306839
|View full text |Cite
|
Sign up to set email alerts
|

Scleral fixation of intraocular lenses using Gore-Tex suture: clinical outcomes and safety profile

Abstract: Ab externo scleral fixation of IOLs with Gore-Tex suture was well tolerated in all cases. No suture-related complications were encountered. This procedure led to improvement in visual acuity and was not associated with significant intraoperative or postoperative complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
148
3
18

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(175 citation statements)
references
References 23 publications
2
148
3
18
Order By: Relevance
“…This was a multicentre study with a mean follow-up of 325 days. While no intraoperative complications were noted, transient hypotony was the commonest postoperative complication seen in 9.4% cases because of incompetence of 23-gauge wounds [8]. Combined 27-gauge PPV and scleral fixation of the Akreos AO60 IOL using Gore-Tex suture, reported in eight eyes with a mean follow-up of 115 days, did not encounter any case of hypotony or sclerotomy site suturing [9].…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…This was a multicentre study with a mean follow-up of 325 days. While no intraoperative complications were noted, transient hypotony was the commonest postoperative complication seen in 9.4% cases because of incompetence of 23-gauge wounds [8]. Combined 27-gauge PPV and scleral fixation of the Akreos AO60 IOL using Gore-Tex suture, reported in eight eyes with a mean follow-up of 115 days, did not encounter any case of hypotony or sclerotomy site suturing [9].…”
Section: Discussionmentioning
confidence: 83%
“…Late suture breakage can be alleviated by using Gore-Tex or 9-0 polypropylene (as was used in this study), which is 60% stronger than 10-0 polypropylene [7]. The Akreos AO60 IOL is soft with no sharp edges on the haptic eyelets, thus decreasing the risk of cutting of suture [8]. A theoretical concern with this technique is that the IOL optical surface may be damaged by folding the IOL with forceps.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitreous hemorrhage and hyphema have also been reported. Published studies have not reported persistent post-operative inflammation, endophthalmitis or suture erosion/breakage at 2 years [27]. With in-the-bag calculations for the IOL, a recent study showed that 2 mm sclerotomies resulted in a more myopic post-operative Secondary Intraocular Lens DOI: http://dx.doi.org/10.5772/intechopen.89569 outcome than 3 mm sclerotomies [28].…”
Section: Scleral Fixation Of Iol With Gore-tex Suture Techniquementioning
confidence: 99%
“…Наиболее распро-страненным и физиологичным методом фиксации ИОЛ признается заднекамерная фиксация, при этом подши-вание ИОЛ осуществляют либо к радужке, либо субскле-рально [3][4][5][6]. В то же время, по данным литературы, ни один из известных способов транссклерального подши-вания ИОЛ не обеспечивает гарантированного, безопас-ного и стабильного ее положения [7][8][9][10][11]. Это и опреде-лило целевые установки данной работы, направленной на разработку и комплексную (клинико-функциональ-ную, субъективную) оценку клинической эффективно-сти оригинальной методики фиксации заднекамерной ИОЛ после ФЭК, осложненной нарушением капсульной поддержки хрусталика.…”
Section: актуальностьunclassified